Radiotherapy in breast cancer patients achieving nodal pathologic complete response after neoadjuvant therapy: a scoping review - Cavalcante, Francisco Pimentel [UNESP]; Cardoso, Amanda; Antonini, Marcelo; Zerwes, Felipe Pereira; Millen, Eduardo Camargo; Mattar, André; Brenelli, Fabrício Palermo; Frasson, Antônio Luiz (AME Publishing Company, 2025)
Background: Neoadjuvant chemotherapy (NAC) is widely accepted as standard treatment in breast cancer, particularly in cases of tumors with aggressive biology. NAC has increased the rates of breast-conserving surgery (BCS) and the conversion of positive axillary nodes detected at initial diagnosis (cN+ to ypN0). In addition, NAC has allowed cases of residual disease to be selected for adjuvant treatments. This new scenario was made possible by innovative neoadjuvant treatments that increase the rate of pathologic complete response (pCR) and significantly change the initial disease volume. A review of concepts is now required, including determining when postmastectomy radiotherapy (PMRT) and regional nodal irradiation (RNI), traditionally indicated in function of the disease volume at the time of diagnosis, should be recommended. Methods: This scoping review discusses contemporary studies, including the recent National Surgical Adjuvant Breast and Bowel Project (NSABP) B-51, regarding the indication of PMRT and RNI following NAC, focusing on cases in which axillary pCR is achieved. Results: Fifteen retrospective cohort studies, one prospective cohort study, and the NSABP B-51, a randomized controlled trial, were included in the review. Most of the studies (n=10) evaluated PMRT alone, while 4 evaluated PMRT and RNI, and 3 analyzed only RNI. Conclusions: The current findings suggest that in cases of axillary pCR (ypN0) obtained after NAC treatment, in patients with breast cancer who had initially been diagnosed with positive axillary nodes (cT1-3 cN1 M0) no benefit is gained from PMRT or RNI. Conversely, in cases of initially more advanced clinical staging (cT4 cN2/3) or residual lymph node disease, radiotherapy should be recommended. Further studies are required to confirm these findings and the possibility of de-escalating radiotherapy according to patient response following NAC.